PH‐Controlled Supramolecular Self‐Assembly of Naphthalenediimide Appended l‐Alanine and Ethylenediamine Asymmetric Bolaamphiphile. Issue 8 (13th July 2021) - Shaikh, Dada B.; Aljabri, Mahmood D.; Nadimetla, Dinesh N.; Birajdar, Shailesh S.; Kobaisi, Mohammad Al; Bhosale, Rajesh S.; Antolasic, Frank; Bhosale, Sidhanath V.; Bhosale, Sheshanath V.
Abstract: Design, synthesis and characterization of novel (2 S )‐2‐[7‐(2‐aminoethyl)‐1, 3, 6, 8‐tetraoxo‐3, 6, 7, 8‐tetrahydrobenzo[ lmn ][3, 8]phenanthrolin‐2(1 H )‐yl]propanoic acid (1 ) bolaamphiphile, which combine naphthalene diimide (NDI) appended with l ‐alanine at one end of imide and ethylenediamine at the other end. An l ‐alanine bearing NDI‐based asymmetric bolaamphiphile self‐assembled at various pH ranging from 2 to 10 forms a variety of supramolecular nanostructures. The UV‐Vis and emission spectroscopic techniques employed for the optical and photophysical properties study of bolaamphiphile 1 at various pH values. It was revealed that the change in pH alters both the optical and photophysical properties of bolaamphiphile 1 . Theoretical calculations used to investigate the electronic properties of the bolaamphiphile 1 . Dynamic light scattering experiments displayed formation of aggregates in solution and scanning electron microscopy (SEM) was used to visualize the nanostructures formed on silicon wafers. Furthermore, the X‐ray diffraction was used to determine the nanostructure's packing properties i. e . crystalline/amorphous. Experimental circular dichroism (CD) spectroscopy results inferred and revealed the induction of chirality into the supramolecular systems, which was shown to be pH dependent. This study clearly demonstrates the manipulation of pH can control/tune chiral supramolecular structures and provide future methods for the development of chiral recognition and catalysis study. Abstract :